Observed mechanisms activating the recent subpolar North Atlantic Warming since 2016 - Chafik, Léon; Penny Holliday, N.; Bacon, Sheldon; Baker, Jonathan A.; Desbruyères, Damien; Frajka-williams, Eleanor; Jackson, Laura C. (Philosophical Transactions of the Royal Society A: Mathematical, Physical and Engineering Sciences, 2023)
The overturning circulation of the subpolar North Atlantic (SPNA) plays a fundamental role in Earth’s climate variability and change. Here, we show from observations that the recent warming period since about 2016 in the eastern SPNA involves increased western boundary density at the intergyre boundary, likely due to enhanced buoyancy forcing as a response to the strong increase in the North Atlantic Oscillation since the early 2010s. As these deep positive density anomalies spread southward along the western boundary, they enhance the North Atlantic Current and associated meridional heat transport at the intergyre region, leading to increased influx of subtropical heat into the eastern SPNA. Based on the timing of this chain of events, we conclude that this recent warming phase since about 2016 is primarily associated with this observed mechanism of changes in deep western boundary density, an essential element in these interactions. This article is part of a discussion meeting issue ‘Atlantic overturning: new observations and challenges’.